MODELS OF ENTERPRISE DEVELOPMENT MANAGEMENT (Development Service Industry Management, 2025)
The article is dedicated to the analysis of enterprise development management in the context of modern economic challenges, particularly the impact of war, crisis situations, and global economic changes on business efficiency. A detailed analysis of the theoretical foundations of change management is conducted, focusing on the need to integrate adaptive strategies into management practices. Among the main theoretical approaches, models are discussed that enable enterprises to respond flexibly to changes in the external environment. One such model is the McKinsey 7-S model, which emphasizes the importance of synchronizing strategy, structure, systems, management style, employees, skills, and shared values to achieve high efficiency and business success. Furthermore, the article discusses John Kotter’s change management model, which outlines the stages that help enterprises successfully implement changes in organizational culture and internal processes. The benchmarking technology is also studied as a tool for comparing and improving business processes.An important aspect is the consideration of external and internal factors influencing enterprise development, such as changes in the economic environment, political risks, innovations, and technological transformations. The author emphasizes the necessity of continuous monitoring of changes and forecasting future trends to make informed managerial decisions. The article also focuses on the specifics of enterprise development management in the context of war and economic instability. Since many enterprises face problems related to resource constraints, security risks, and changes in product demand, the author offers a number of recommendations to improve enterprise resilience, including product diversification, cost optimization, and improvement of personnel management processes. In general, the article presents theoretical and practical recommendations for enhancing enterprises' adaptability to changes in the external environment, contributing to their economic stability and competitiveness in the face of global challenges.**
Keywords: development management; enterprises; adaptation to change; change management model